Identification of an Inducible Bacteriophage in a Virulent Strain of Streptococcus suis Serotype 2 - Harel, J. (American Society for Microbiology, 2003)
Streptococcus suis infection is considered to be a major problem in the swine industry worldwide. Most virulent Canadian isolates of S. suis serotype 2 do not produce the known virulence markers for this pathogen. PCR-based subtraction hybridization was adapted to isolate unique DNA sequences which were specific to virulent strains of S. suis isolated in Canada. Analysis of some subtracted DNA clones revealed significant homology with bacteriophages of gram-positive bacteria. An inducible phage (named Ss1) was observed in S. suis following the incubation of the virulent strain 89-999 with mitomycin C. Phage Ss1 has a long noncontractile tail and a small isometric nucleocapsid and is a member of the Siphoviridae family. Ss1 phage DNA appears to be present in most Canadian S. suis strains tested in this study, which were isolated from diseased pigs or had proven virulence in mouse or pig models. To our knowledge, this is the first report of the isolation of a phage in S. suis.